Strategic voting over strategic proposals - Philip Bond; Hülya Eraslan (The Johns Hopkins University, Department of Economics, 2008)
Prior research on 'strategic voting' has reached the conclusion that unanimity rule is uniquely bad: it results in destruction of information, and hence makes voters worse off. We show that this conclusion depends critically on the assumption that the issue being voted on is exogenous, i.e., independent of the voting rule used. We depart from the existing literature by endogenizing the proposal that is put to a vote, and establish that under many circumstances unanimity rule makes voters better off. Moreover, in some cases unanimity rule also makes the proposer better off, even when he has diametrically opposing preferences. In this case, unanimity is the Pareto dominant voting rule. Voters prefer unanimity rule because it induces the proposing individual to make a more attractive proposal. The proposing individual prefers unanimity rule because the acceptance probabilities for moderate proposals are higher. We apply our results to jury trials and debt restructuring.
Keywords: C7; D7; D8; 330; Strategic voting; agenda setting; multilateral bargaining; Wahlverhalten; Abstimmungsregel; Strategie; Verhandlungstheorie; Theorie